2001
DOI: 10.1001/archpedi.155.11.1243
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pica Prevalence Among Patients With Sickle Cell Disease

Abstract: Pica appeared to have an unusually high prevalence in patients with sickle cell disease and a correlation with lower Hb levels. It is unclear whether pica is a specific marker of disease severity, because our review did not show a relationship to increased number and duration of hospitalizations. The association between pica and low body weight suggests a nutritional effect on its prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 11 publications
3
23
0
2
Order By: Relevance
“…This is concurrent with the findings of Ivascu et al (21) in a study on patients with sickle cell disease but disagrees with the findings of Nchito et al which showed a significant incidence of pica in girls in their study from Zambia (22). …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This is concurrent with the findings of Ivascu et al (21) in a study on patients with sickle cell disease but disagrees with the findings of Nchito et al which showed a significant incidence of pica in girls in their study from Zambia (22). …”
Section: Discussionsupporting
confidence: 50%
“…In a study of Zambian children, 74.4% practiced some form of geophagia (21). In a study in Egypt, clay (43.1%) and dust (25.9%) were the most common type of pica (19).…”
Section: Discussionmentioning
confidence: 99%
“…Pica is a known problem in children with sickle cell disease [1][2][3][4][5]. Ingestion of a variety of nonnutritive materials can result in intestinal obstruction and perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of a variety of nonnutritive materials can result in intestinal obstruction and perforation. A relationship between pica and iron or zinc deficiency has been demonstrated [1][2][3]. Zinc oxides are used as curing agents in the manufacture of polyurethane foam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation